Descriptive analysis of low versus elevated intracranial pressure on cerebral physiology in adult traumatic brain injury: a CENTER-TBI exploratory study - Zeiler, Frederick A.; Ercole, Ari; Cabeleira, Manuel; Stocchetti, Nino; Hutchinson, Peter J.; Smielewski, Peter; Czosnyka, Marek; Anke, Audny; Beer, Ronny; Bellander, Bo-Michael; Beqiri, Erta; Buki, Andras; et al. (Acta neurochirurgica, 2020)
To date, the cerebral physiologic consequences of persistently elevated intracranial pressure (ICP) have been based on either low-resolution physiologic data or retrospective high-frequency data from single centers. The goal of this study was to provide a descriptive multi-center analysis of the cerebral physiologic consequences of ICP, comparing those with normal ICP to those with elevated ICP.